Spectrophotometric method for simultaneous determination of valsartan and substances from the group of statins in binary mixtures - Stolarczyk Mariusz; Apola Anna; Maślanka Anna; Kwiecień Anna; Opoka Włodzimierz (Acta Pharmaceutica)
Applicability of derivative spectrophotometry for the determination of valsartan in the presence of a substance from the group of statins was checked. The obtained results indicate that the proposed method may be effective by using appropriate derivatives: for valsartan and fluvastatin - D1, D2 and D3, for valsartan and pravastatin - D1 and D3, for valsartan and atorvastatin - D2 and D3. The method was characterized by high sensitivity and accuracy. Linearity was maintained in the following ranges: 9.28-32.48 mg mL-1 for valsartan, 8.16-28.56 mg mL-1 f or fluvastatin, 14.40-39.90 mg mL-1 for atorvastatin and 9.60-48.00 mg mL-1 for pravastatin. Determination coefficients were in the range of 0.989-0.999 depending on the analyte and the order of derivative. The precision of the method was high with RSD from 0.1 to 2.5 % and recovery of individual components was within the range of 100 ± 5 %. The developed method was successfully applied to the determination of valsartan combined with fluvastatin, atorvastatin and pravastatin in laboratory prepared mixtures and in pharmaceutical preparations.